Ancient Egypt : anatomy of a civilization - Kemp, Barry J (Routledge, 2018)
Completely revised and updated to reflect the latest developments in the field, this second edition of Barry J. Kemp's popular text presents a compelling reassessment of what gave ancient Egypt its distinctive and enduring characteristics.